Politics and Mental Health: The ‘Goldwater Rule’ - Ali Madeeh Hashmi (Journal of Pakistan Psychiatric Society, 2022)
...it is for mental health professionals in particular and healthcare workers in general, to not make public pronouncements about specific people (or institutions or political processes) regarding their actual or supposed medical or psychiatric conditions and how doing so can be problematic for any number or reasons.